HERC2 rs12913832 Association with Eye, Hair and Skin Color in The Iraqi Population - Hasan, Jasim Mohammed; Gaaib, Jawdat N.; Mahdi, Mohammed Ghanim (Scientific Journal of Medical Research, 2021)
Objectives: The DNA prediction of the skin, hair, and eye color represents applying for externally visible characteristics (EVCs), which acquire increasing attention in the domain of (FDP) forensic DNA phenotyping. This is primarily due to its capacity to reduce the suspects number without requiring matching DNA recovered from biological material at crime scenes to reference data. However, such a study has not been previously tested on the Iraqi population. Methods: The present study investigated the association of rs12913832 single nucleotide polymorphisms (SNPs) with the eye, hair, and skin color in 200 Iraqi volunteers randomly chosen, they were distributed based on eye, hair, and skin color. The DNA was extracted, The PCR amplification and gel electrophoresis of the PCR products was conducted for the detection of SNP rs12913832. The results were analyzed with the Statistical Package for the Social Sciences (SPSS) program and Chi-Square test. Results: In spite of the externally visible characteristics (EVCs) multifactorial nature that is under the impact of genetic interactions and environmental agents in addition to the small study sample, we announced a great association for the SNP rs12913832 with the eye, hair, and skin color. Conclusion: The findings of our study assure the results of previous studies the association of rs12913832 SNP with skin, hair, and eye color.